Cytotoxic effects of Fisturalin-3 and 11-Deoxyfisturalin-3 on Jurkat and U937 cell lines - Mijares, Michael Rodney; Ochoa, Mariana; Barroeta, Amairelys; Martinez, Gricelis Patricia; Suarez, Alirica Isabel; Compagnone, Reinaldo Santi; Chirinos, Perla; Avila, Ramona; De Sanctis, Juan Bautista (Biomedical papers, 2013)
Background: Fisturalines are bromotyrosine compounds isolated from marine sponges. Previous studies have shown antineoplasic, antiviral and antibacterial effects in Vitro; however, the possible effects of these compounds in hematologic malignancies have not been assessed.Methods: In the present study, the antiproliferative and pro apoptotic effects of Fistularin-3 (F) and 11-Deoxyfistularin-3 (DF) were assessed using the MTT method and annexin V/propidium iodide by flow cytometry using the cell lines: Jurkat E6.1 and U937. In addition, the cell cycle was assessed by flow cytometry.Results: Inhibition of the proliferative response was concentration and time dependent. The IC50 of F was 7.39 and 8.10 uM for Jurkat E6.1 and U937 respectively. At 24 and 48 h, in the U937 cell line, but not in the Jurkat cell line, both compounds induced up to 35% annexin V increase. Necrosis was not observed in any case. Compound F induced, in both cell lines, a decrease in the number of cells in the S phase and increase in the G0/G1 phase. In the Jurkat cell line only, there was an increase in the number of cells in the G2/M phase. Compound DF was not as effective as F.Conclusions: F is more active than DF in repressing the cell cycle and inducing apoptosis. Both compounds are potentially useful in the development of new drugs to treat hematologic malignancies.
Keywords: Fistularin-3; 11-Deoxyfistularin-3; leukemia; cancer; bromotyrosine; quercetin; Aplysina fistularis